European Association of Neuro-Oncology (EANO) guidelines for treatment of primary central nervous system lymphoma (PCNSL). Issue 1 (12th August 2022) - Hoang-Xuan, Khê; Deckert, Martina; Ferreri, Andrés J M; Furtner, Julia; Gallego Perez-Larraya, Jaime; Henriksson, Roger; Hottinger, Andreas F; Kasenda, Benjamin; Lefranc, Florence; Lossos, Alexander; McBain, Catherine; Preusser, Matthias; et al.
Abstract: The management of primary central nervous system (PCNSL) is one of the most controversial topics in neuro-oncology because of the complexity of the disease and the limited number of controlled studies available. In 2021, given recent advances and the publication of practice-changing randomized trials, the European Association of Neuro-Oncology (EANO) created a multidisciplinary task force to update the previously published evidence-based guidelines for immunocompetent adult patients with PCNSL and added a section on immunosuppressed patients. The guideline provides consensus considerations and recommendations for the treatment of PCNSL, including intraocular manifestations and specific management of the elderly. The main changes from the previous guideline include strengthened evidence for the consolidation with ASCT in first-line treatment, prospectively assessed chemotherapy combinations for both young and elderly patients, clarification of the role of rituximab even though the data remain inconclusive, of the role of new agents, and the incorporation of immunosuppressed patients and primary ocular lymphoma. The guideline should aid the clinicians in everyday practice and decision making and serve as a basis for future research in the field.